Improvement of Learning Outcomes How to Maintain Blood Circulation Organ Through The Cooperative Learning Method of Class 5th Students - Lis Setyawati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to determine the improvement of learning outcomes in Theme 4 Sub-theme 3 Ways to Maintain Circulatory Organs with the Cooperative Learning method for 5th grade students of SD Negeri Soneyan 03 Margoyoso Pati for the 2020/2021 academic year. The form of this research is Classroom Action Research which is carried out in three cycles. The learning improvement that is carried out is an action to improve the pre-cycle learning outcomes that have not achieved the learning objectives as expected by the researcher. In cycle 1, the result is that only 55.56% and 44.44% complete students are still incomplete. In cycle 2, the result is 83.33% of students have reached the completeness and 16.67% have not been completed. In cycle 3, the result was that the completeness percentage reached 88.89% and the incomplete percentage was only 11.11%. From the research results indicate an increase in student learning outcomes on theme 4 sub-themes 3. This proves that the Cooperative Learning method is able to improve student learning outcomes.